Effect of Varying Chitosan Molecular Weights on the Morphology and Physical Characteristics of PVA/Chitosan Composite Hydrogels - Sihombing, Yuan Alfinsyah; Luthfianti, Halida Rahmi; Waresindo, William Xaveriano; Rodhiyah, Marathur; Nafisah, Nur’aini; Hapidin, Dian Ahmad; Edikresnha, Dhewa; Khairurrijal, Khairurrijal (Makara Journal of Science, 2025)
We employed the innovative freeze–thaw method to investigate the effect of chitosan (CS) molecular weights incorporated into polyvinyl alcohol on the morphology and physical characteristics of the hydrogel. This study aimed to unravel the intricate relationships between CS molecular weight variations, CS concentration, and the number of freeze–thaw cycles (4 or 6 cycles) on hydrogel swelling degree and weight loss. Incorporating CS improved the hydrogel structure and enhanced its porosity, resulting in remarkable increases in swelling degree ranging from 2 to 6 times the initial weight. Higher molecular weight CS (310,000–375,000 Da) exhibited a lower swelling degree than medium molecular weight CS (190,000–310,000 Da), attributed to its ability to prevent crystal formation during the freeze–thaw process. Increased freeze–thaw cycles led to a decreased swelling degree, which indicated enhanced rigidity and stability due to more significant hydrogen bond formation with hydroxyl groups. Higher CS content amplified hydrogel weight loss, and additional cycles accentuated this effect, highlighting the challenge of maintaining an effective gel structure. CS with medium molecular weight emerged as the more suitable choice for applications demanding superior water absorption.